2007
DOI: 10.4049/jimmunol.178.4.2287
|View full text |Cite
|
Sign up to set email alerts
|

Fas Receptor Clustering and Involvement of the Death Receptor Pathway in Rituximab-Mediated Apoptosis with Concomitant Sensitization of Lymphoma B Cells to Fas-Induced Apoptosis

Abstract: Ab binding to CD20 has been shown to induce apoptosis in B cells. In this study, we demonstrate that rituximab sensitizes lymphoma B cells to Fas-induced apoptosis in a caspase-8-dependent manner. To elucidate the mechanism by which Rituximab affects Fas-mediated cell death, we investigated rituximab-induced signaling and apoptosis pathways. Rituximab-induced apoptosis involved the death receptor pathway and proceeded in a caspase-8-dependent manner. Ectopic overexpression of FLIP (the physiological inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 36 publications
3
63
1
Order By: Relevance
“…However, the molecular connection between JNK and fasL in our experiments was still unclear. It has recently been reported that rituximab (chimeric anti-CD20 Ab) sensitizes the non-Hodgkin lymphoma cell line to fas-induced apoptosis in association with modulation of p38 MAP kinase and NF-B (42). Further molecular studies should be conducted to elucidate how EBV-transformed B cells would be sensitized to fas-induced apoptosis following cross-linking of B7-H1.…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular connection between JNK and fasL in our experiments was still unclear. It has recently been reported that rituximab (chimeric anti-CD20 Ab) sensitizes the non-Hodgkin lymphoma cell line to fas-induced apoptosis in association with modulation of p38 MAP kinase and NF-B (42). Further molecular studies should be conducted to elucidate how EBV-transformed B cells would be sensitized to fas-induced apoptosis following cross-linking of B7-H1.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, cotreatment with rituximab and recombinant human sTRAIL synergistically activates apoptosis (4). Analogously, we and others have recently shown that cotreatment with rituximab and an agonistic anti-Fas mAb also synergistically activates apoptosis in malignant B cells (5,6). Importantly, although clinical use of anti-Fas antibodies is deemed impossible due to liver toxicity (7)(8)(9), the potential feasibility of exploiting Fas apoptotic signaling using soluble Fas ligand (sFasL) has recently been reestablished (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with another recent study demonstrating the significance of ligand-independent death receptor clustering in the sensitization to Fas-mediated apoptosis and overcoming of Fas resistance. 40 Also, the observation that LY30 can sensitize Jurkat and HT29 cells to TRAIL indicates that our findings might be relevant across different tumor cell types. Taken together, this work highlights the tremendous potential of LY30 in priming tumor cells for TRAIL-mediated killing, and could have implications for the design of novel strategies to overcome the problem of TRAIL resistance in tumor cells.…”
Section: Resultsmentioning
confidence: 67%